Do External Supports Improve Dynamic Balance in Patients with Chronic Ankle Instability? A Network Meta-analysis. Issue 2 (February 2020) - Tsikopoulos, Konstantinos; Sidiropoulos, Konstantinos; Kitridis, Dimitrios; Cain ATC, Spencer M.; Metaxiotis, Dimitrios; Ali, Ashique
Abstract: Background: To improve ankle stability in patients who have experienced an ankle sprain with residual symptoms of instability and/or objective joint laxity, external supports (such as taping, bracing, and orthotic insoles) are used sometimes. However, available randomized trials have disagreed on whether restraints improve balance in those individuals. In this situation, a network meta-analysis can help because it allows for comparing multiple treatments simultaneously, taking advantage not only of direct but also indirect evidence synthesis. Questions/purposes: The aim of this network meta-analysis was to assess (1) the impact of taping and orthotic devices on dynamic postural control in individuals with ankle instability and (2) the presence of a placebo effect in participants treated with sham taping and complications resulting from the administered treatments. Methods: We searched the PubMed, Scopus, and CENTRAL databases up to February 13, 2019 for completed studies. Randomized trials assessing the results of real and/or sham taping, wait-and-see protocols, ankle bracing, and foot orthotics for ankle instability as determined by one or more ankle sprains followed by ongoing subjective symptoms and/or mechanical laxity were included. We evaluated dynamic postural control in terms of the Star Excursion Balance Test in the posteromedial direction (SEBT-PM), which is considered the most representative of balance deficits in patients with ankle instability. Standardized mean differences were re-expressed to percentage differences in SEBT-PM, with higher scores representing possible improvement. Subsequently, those data were checked against the established minimal detectable change of 14% for this scale to make judgements on clinical importance. We also assessed the presence of a placebo effect by comparing the results of sham taping with no treatment and complications resulting from the administered treatments. Additionally, we judged the quality of trials using the Cochrane risk of bias tool and quality of evidence using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach. A total of 22 trials met our inclusion criteria, 18 of which were deemed to be at a low risk of bias. A network of treatments consisting of 13 studies was created, and the level of evidence was judged to be high. As far as participants' allocation to treatment arms, 85 patients followed a wait-and-see protocol, 29 received placebo taping, 99 were treated with taping, 16 were treated with bracing, 27 were administered insoles, and six individuals were offered a combination of insoles with bracing. Of note, with statistical power set at 80%, a minimum of 16 patients per treatment group was required to provide sufficient statistical power and detect a SEBT-PM percentage difference of 14%. Results: A network meta-analysis did not demonstrate a benefit of taping or bracing over no treatment (percentage difference in SEBT-PM between taping and bracing versus control: -2.4 [95% CI -6 to 1.1]; p = 0.18, and -7.5 [95% CI -15.9 to 1]; p = 0.08, respectively). This was also the case for sham taping because the measurement increase failed to exceed the minimal detectable change (percentage difference in SEBT-PM between sham taping and untreated control: -1.1 [95% CI -6.9 to 4.7]; p = 0.72). Importantly, there were no reported adverse events after treatment application. Conclusions: Evidence of moderate strength indicated that external supports of any type were no more effective than controls in improving dynamic postural control in patients with at least one ankle sprain and residual functional or mechanical deficits. Therefore, implementing those tools as a standalone treatment does not appear to be a viable strategy for the primary management of ankle instability. It is conceivable that combinations of rehabilitation and external supports could be more effective than external supports alone, and future trials should evaluate the potential of such combinations in enhancing not only clinician-reported but also patient-oriented outcomes using long-term follow-up measurements. Level of Evidence: Level I, therapeutic study.